The Effectiveness of Psychoeducation on Depression Literacy and Psychological Well-being of University Students - Rathi, Sayema Rahman; Prince, Md Abu Hurayra; Baroi, Bijon; Hossan, Md Rony; Roy, Kishor; Muhammad, Noor (Jagannath University Journal of Science, 2024)
Today’s modern life is a challenging issue for human beings, particularly those who have mental illnesses like depression, requiring awareness-related programs for increasing their Depression Literacy (D-Lit) and Psychological Well-being (PWB). To mark the gap, we planned to investigate the effect of web-based psychoeducation on literacy regarding depression and psychological well-being. A total of 100 depressed students were included in the sampling frame, purposively selected based on some inclusion and exclusion criteria from Jagannath University. The study was accomplished by following a pretest-posttest with a control group design where data were collected using Depression, Depression Literacy (D-Lit), and Psychological Well-being questionnaires along with a personal information form. The data were analyzed by applying an independent sample t-test, paired sample t-test, and ANCOVA. Results revealed that the level of D-Lit and PWB of the depressed students significantly increased in the post-test as compared to the pre-test in the experimental group, but no significant changes in the control group, indicating psychoeducation has an effect on increasing D-Lit and PWB. This finding explored that psychoeducation can be an immediate awareness program for improving depression-related knowledge and psychological well-being in the community. The applications of these outcomes for investigation and practice are discussed. Jagannath University Journal of Science, Volume 10, Number I, Jun 2023, pp. 1−10